UPAYA BRANDING UMKM KELURAHAN DUKUH SUTOREJO DENGAN PEMBUATAN DESAIN LOGO DAN KARTU NAMA - Diana, Laksmi; Putri Amini, Novira; Dlonni Dahlan, Ahsan; Revandra, Muhammad; Putri T, Ananda Harum (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2022)
Micro Small and Medium Enterprises (UMKM) are the spearhead for economic development. There are many indicators that influence the success of an MSME in competing such as good product quality, attractive packaging, logos and business cards as product identities, satisfactory service and other indicators. Some MSMEs in Dukuh Sutorejo Village have problems such as branding and digital marketing. Departing from these obstacles, community service activities through the UPN Veterans East Java Thematic KKN program, the writing team helped several MSMEs in overcoming these obstacles, one of which was Making Logo Designs and Business Cards, with the aim of improving the quality of MSMEs so that they are more ready to survive amid MSME competition. tall one. The method used in this community service activity is data collection through interviews and observations. The result of this community service activity is the creation of logo designs and business cards that make identities for several UMKM in Dukuh Sutorejo Village.